Using complete blood count markers to predict febrile seizures - Maulena, Ufik; Udin, Muchammad Fahrul (Paediatrica Indonesiana, 2025)
Background The complete blood count test includes some markers of inflammation. Febrile seizures have been associated with inflammatory processes. Objective To investigate for possible relationships between the occurrence of febrile seizures (FS) and complete blood count (CBC) parameters. Methods Two hundred children aged 6-60 months presenting with fever at the Emergency Department between January 2022–August 2023 were included. These subjects were divided into a febrile seizures group (n = 100) and a control fever without seizures group (n =100). Demographic and complete blood count data were compared using logistic regression test. Results The frequency of febrile seizures was significantly higher in younger children [mean age 23.89 (SD 15.88) months]. The febrile seizures group had lower lymphocyte counts but significantly higher white blood cell (WBC), neutrophils, platelets, neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) values than the control group. Multivariate analysis revealed that NLR (OR=0.84; P=0.001), PLR (OR=0.939; P=0.001), WBC (OR =0.773; P=0.001), neutrophil- platelet ratio (NPR) (OR=0.000; P=0.001), platelets (PLT) (OR=0.996; P=0.017), lymphocytes (OR=1.239; P=0.0001), and neutrophils (OR=1.047; P=0.022) had significant associations with febrile seizures while other parameters did not. Conclusion Patients with febrile seizures had significantly higher levels of inflammatory markers, such as NLR, PLR, WBCs, PLTs, neutrophils, and NPR, and lower levels of lymphocytes than children with fever but no seizures, as determined by complete blood count findings.